Level of Acceptability of Computer-Assisted Assessment (CAA) and Student’s Academic Performance in Key Stage 2 of Ilalim Elementary School for The School Year 2022-2023 - Agoja, Jr., Jesse S.; Albino, Michael G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In this research study, the researcher aimed to determine the level of acceptability of computer-assisted assessment and learners’ academic performance of 127 Key Stage 2 Learners of Ilalim Elementary School for the School Year 2022-2023. A descriptive survey instrument was used to determine the level of acceptability adapted from the computer-based assessment acceptance model (CBAAM) and was modified by the researcher. Data revealed that the use of computer-assisted assessment of the Key Stage 2 learners was Moderately Acceptable with a mean of 4.01, indicating that the application purposively used it to improve their knowledge and skills. The learners gained an Outstanding academic performance as reflected in their general weighted average from the four grading periods. Significant differences were found in the level of acceptability of the use of computer-assisted assessment on the profile variables of the learner-respondents. Moreover, the results showed a positive correlation between the level of acceptability of the use of computer-assisted assessment on the learner’s academic performance. Based on the gathered data from the survey, computer-assisted assessment provides the learners with a positive experience when using the application through its friendly user interface. Teachers may continue to use the computer-assisted assessment application to motivate their learners to increase their engagement in learning their subject. It is recommended that teachers may further enhance the delivery of questions in the CAA application to improve learners’ academic performance in the future.